Peranan Akomodasi Resort dan Potensi Masyarakat Desa sebagai Penunjang Destinasi Tamansari Ciapus Bogor Jawa Barat - Yustisia Pasfatima Mbulu (Journal of Tourism Destination and Attraction, 2013)
Tourist destination must have four components which include tourist attractions, good accessibility, availability of various facilities, such as accommodation, restaurants, shopping and other services and tourism organizations. This study specifically focuses on an emerging tourist destination named Tamansari Ciapus in the city of Bogor, West Java. It aims to examine the roles of a resort accommodation, located in the area, in supporting the new destination. The study also wants to look at the roles and potential of local village communities in developing community-based tourism destination. It uses descriptive qualitative method of data collection through surveys, field observations and interviews. This study reveals that the role of resort accommodation, in this case the Highland Park Hotel, is quite important in the development of Tamansari Ciapus as a new destinaton. In many case, the resort is the very reason the visitors come to the area. However, such a role is not yet optimum as there is not yet a cooperation between the resort, other attraction owners in the area (silk, mushroom cultivation, and other home industries) and also the local community. The resort guests, for instance, seldom visit areas outside the resort. The role of the community is also quite significant in developing the area as a village tourism destination. Community organizations has been formed and tour packages have been developed although the market is still limited. Other issues that need to be addressed includes the lack of tour guides, integrated souvenir centers and professionally-managed homestay.